Multi-model simulations of the impact of international shipping on Atmospheric Chemistry and Climate in 2000 and 2030 - Eyring, V.; Lauer, A.; Stevenson, D.S.; Dentener, F.J.; Butler, T.; Lawrence, M.G.; Collins, W.J.; Sanderson, M.; Ellingsen, K.; Gauss, M.; Isaksen, I.S.A.; Hauglustaine, D.A.; et al. (Office for Official Publications of the European Communities, Luxembourg, 2007)
The global impact of shipping on atmospheric chemistry and radiative forcing, as well as the associated uncertainties, have been quantified using an ensemble of ten state-of-the-art atmospheric chemistry models and a pre-defined set of emission data. The analysis is performed for present-day conditions (year 2000) and for two future ship emission scenarios. In one scenario emissions stabilize at 2000 levels; in the other emissions increase with a constant annual growth rate of 2.2% up to 2030 (termed the ‘Constant Growth Scenario’). The first key question addressed by this study is how NOx and SO2 emissions from international shipping might influence atmospheric chemistry in the next three decades if these emissions increase unabated. The models show future increases in NO2 and ozone burden which scale almost linearly with increases in NOx emission totals. For the same ship emission totals but higher emissions from other sources a slightly smaller response is found. The most pronounced changes in annual mean tropospheric NO2 and sulphate columns are simulated over the Baltic and North Seas; other significant changes occur over the North Atlantic, the Gulf of Mexico and along the main shipping lane from Europe to Asia, across the Red and Arabian Seas. The second key issue was to examine the range of results given by the individual models compared to the ensemble mean. Uncertainties in the different model approaches in the simulated ozone contributions from ships are found to be significantly smaller than estimated uncertainties stemming from the ship emission inventory, mainly the ship emission totals, the neglect of ship plume dispersion, and the distribution of the emissions over the globe.